Preparation method of polyoxyethylene / amphoteric polyion liquid type composite solid electrolyte

By introducing zwitter polyion liquid into PEO-based polymer electrolytes and changing the lithium ion coordination environment, the problems of low conductivity and poor stability of PEO-based electrolytes at room temperature are solved, and higher conductivity and electrochemical stability are achieved .

CN119400941APending Publication Date: 2025-02-07HUNAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411384425.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing PEO-based polymer electrolytes have low ionic conductivity at room temperature, and are prone to cracking and decomposition during complex deformation or circulation, and have poor electrochemical stability.

Method used

By introducing zwitter polyion liquid, changing the lithium ion coordination environment, weakening the strong interaction of Li-PEO, polyethylene oxide/zwitter polyion liquid-type composite solid electrolyte is prepared.

Benefits of technology

It improves lithium ion conductivity and electrochemical stability and extends the number of cycles of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400941A_ABST
    Figure CN119400941A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyoxyethylene / amphoteric polyion liquid type composite solid electrolyte. The preparation method comprises the following steps: S1, reacting bromoacetic acid with 1-vinyl imidazole to obtain carboxylic acid functionalized imidazole chlorine salt; s2, adding lithium salt, washing and drying to obtain carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imine salt; s3, adding a LiOH solution, and reacting to obtain hydroxy acid functionalized ionic liquid; s4, adding a photoinitiator solution to obtain amphoteric polyionic liquid; and S5, adding the polyether diolefin polymer into the polyion liquid, sequentially adding LITFSI, tetrakis (3-thiopropionic acid) pentaerythritol tetrathiol, a thiol chain extender and a photoinitiator, and reacting and drying to obtain the polyoxyethylene / amphoteric polyion liquid type solid electrolyte. According to the obtained solid electrolyte, the lithium ion conductivity is improved, the assembled battery has good electrochemical cycle stability, the service life of the battery is prolonged, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid electrolytes, and in particular to a method for preparing a polyethylene oxide / amphoteric polyionic liquid type composite solid electrolyte. Background Art

[0002] Lithium-ion batteries (LIBs) are considered attractive energy storage devices because of their light weight and high energy density. Current commercial lithium-ion batteries (LIBs) use liquid organic electrolytes, which may cause potential dangers such as electrolyte leakage, combustion, and explosion under conditions such as overcharging, short circuiting, or overheating. This has become an obstacle to the further use of lithium-ion batteries and the development of the new energy industry. In this context, polymer solid electrolytes (SPEs) have fundamentally solved safety issues such as explosion and leakage due to their liquid-free characteristics, and have attracted widespread attention from researchers. Polymer solid electrolytes (SPEs) have the characteristics of light weight, good flexibility, easy processing, large-scale manufacturing capabilities, and good electrochemical stability, and can be used as a substitute for liquid electrolytes. By incorporating lithium salts into the polymer matrix, the reliability, stability, and safety of LIBs can be significantly improved without the addition of liquid electrolytes. At present, PEO-based polymer electrolytes have been studied most intensively, and their main implementation scheme is to incorporate the EO part into the polymer chain structure. The most widely used method is copolymerization. EO monomers are mixed with polymers and lithium salts, and polymerization is initiated under experimental conditions such as light and heat without the addition of liquid electrolytes. However, the ionic conductivity of PEO-based polymer electrolytes currently available at room temperature is low, only about 10 -6 -10 -7 S cm-1, high ionic conductivity can only be achieved at around 60°C; secondly, since the electrolyte is solid, the interface stability between the electrolyte and the electrode is much worse than that of liquid electrolytes. It is easy to crack and decompose during complex deformation or cycling, and has poor electrochemical stability.

[0003] CN117219753A discloses a polyethylene oxide solid-state lithium battery positive electrode material and a preparation method thereof and a battery containing the same, wherein the positive electrode material comprises a positive electrode material body and a coating layer coated on the outer layer of the positive electrode material body, wherein the material of the coating layer comprises Li1+x-yNbl-x-3yTix+4yO3 (0.05≤x≤0.3,0≤y≤0.182), and the Ti element and Nb element in the coating layer diffuse into the lattice of the positive electrode material body during the cycle; based on the total weight of the polyethylene oxide solid-state lithium battery positive electrode material, the mass fraction of the coating layer is 0.2% to 2%, and the thickness of the coating layer is 3-20nm. The battery assembled by this scheme exhibits cracking and attenuation after 300 cycles, and the electrochemical stability is also poor. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing a polyethylene oxide / amphoteric polyionic liquid type composite solid electrolyte.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte comprises the following steps:

[0007] S1. bromoacetic acid and 1-vinylimidazole are added to anhydrous ethanol for reaction, and then dried to obtain carboxylic acid functionalized imidazole chloride;

[0008] S2. The carboxylic acid functionalized imidazole chloride salt is configured into a 30% aqueous solution, and a 30% aqueous solution of a lithium salt in the same amount is added to the aqueous solution, and the carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imide salt is obtained after drying;

[0009] S3. adding LiOH solution to the carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imide salt to obtain a hydroxy acid functionalized ionic liquid after reaction;

[0010] S4. dissolving the hydroxy acid functionalized ionic liquid and the photoinitiator in anhydrous methanol and irradiating with ultraviolet light for 10 to 30 minutes to obtain a polyionic liquid;

[0011] S5. Add the polyether diene polymer to the polyionic liquid, and then add LITFSI, tetrakis(3-mercaptopropionic acid)pentaerythritol (PETMP), thiol chain extender, and photoinitiator in sequence, and add dropwise into the mold after stirring. After ultraviolet irradiation, dry and obtain a polymer solid electrolyte.

[0012] Furthermore, the molar ratio of bromoacetic acid to 1-vinylimidazole is 1:1.

[0013] Furthermore, the reaction conditions of S1 are: reacting for 40 to 58 hours under nitrogen protection; and the drying conditions are: constant temperature of 55 to 65° C. and insulation time of 72 to 84 hours.

[0014] Furthermore, in S3, the molar ratio of the carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imide salt to LiOH is 1:0.7-1.7.

[0015] Furthermore, the mass ratio of IL to photoinitiator in S4 is 1:0.005-0.015

[0016] Furthermore, the polyether diene polymer is PEGDA, and its weight average molecular weight is 200-5000.

[0017] Furthermore, the thiol chain extender is one or more of 2,3-butanedithiol, 1,6-hexanedithiol, 1,2-ethanedithiol, 2-methyl-3-tetrahydrofuranthiol, and 1,3-propanedithiol.

[0018] Furthermore, the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and 2,4-dihydroxybenzophenone.

[0019] Furthermore, in the S5, the molar ratio of LITFSI, tetrakis(3-mercaptopropionic acid)pentaerythritol, thiol chain extender, and photoinitiator is 13.5:2:13.5:0.01.

[0020] A solid electrolyte battery obtained by the above preparation method.

[0021] Compared with the prior art, the beneficial effects are:

[0022] The present invention introduces amphoteric polyionic liquid into the system of traditional PEO-based electrolyte. The introduction of amphoteric polyionic liquid causes competitive interaction, and the lithium ion coordination environment is changed from the original coordination of Li-PEO only to the coordination of Li-ZwitPIL-PEO, thereby weakening the strong interaction of Li-PEO, thereby improving the lithium ion conductivity and electrochemical stability, and increasing the number of battery cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The carboxylic acid functionalized trifluorosulfonic acid imide salt (COOH-IL [TFSI] ) Hydrogen spectrum of the product;

[0024] Figure 2 This is the hydrogen spectrum of the polyionic liquid PIL in Example 1 of the present invention;

[0025] Figure 3 A schematic diagram of the conductivity of the polyethylene oxide / amphoteric polyionic liquid solid electrolyte prepared in embodiments 1, 2, and 3 of the present invention;

[0026] Figure 4 The electrochemical impedance spectra of the polyethylene oxide / amphoteric polyionic liquid solid electrolyte prepared in embodiments 1, 2, and 3 of the present invention;

[0027] Figure 5 This is a linear sweep voltammetric curve of the polyethylene oxide / amphoteric polyionic liquid solid electrolyte prepared in Example 1 of the present invention;

[0028] Figure 6This is a charge and discharge cycle test diagram of a Li / SPE / Li symmetrical battery composed of solid electrolytes in Example 1 of the present invention;

[0029] Figure 7 The charge-discharge cycle test diagram of a pure PEO-based electrolyte combined into a Li / SPE / Li symmetric battery;

[0030] Figure 8 This is a digital photo of the polyethylene oxide / amphoteric polyionic liquid solid electrolyte film prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following examples are further explained and illustrated, but the specific examples do not limit the present invention in any form. Unless otherwise specified, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are conventional commercially available raw materials.

[0032] Example 1

[0033] This embodiment provides a method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte, comprising the following steps:

[0034] Bromoacetic acid and 1-vinyl imidazole were added to anhydrous acetonitrile in a molar ratio of 1:1, and the reaction was carried out under nitrogen protection for 48 hours. After the experiment, the vacuum filtration was repeated three times with ethyl acetate. After drying at 60°C for 3 days, the carboxylic acid functionalized imidazole chloride (COOH-IL [Cl] ), COOH-IL [Cl] Prepare a 30% aqueous solution, and use a constant pressure funnel to replace anions with a 30% aqueous solution of lithium salt (LiTFSI) of the same substance. After completion, wash it with pure water for 3 times and freeze-dry it for 12 hours to obtain a carboxylic acid functionalized trifluorosulfonic acid imide salt (COOH-IL [TFSI] ). Using lithium hydroxide to react COOH-IL [TFSI] The IL and the photoinitiator were dissolved in anhydrous methanol and irradiated with ultraviolet light for 20 minutes to obtain the polyionic liquid PIL, which was then stored in a vacuum drying oven at 60°C.

[0035] First, 0.05 g of PIL was dissolved by ultrasonic stirring with 0.4 g of PEGDA (MW2000), and then 0.1 g of LITFSI, 0.015 g of tetrakis(3-mercaptopropionic acid) pentaerythritol (PETMP), 0.292 g of thiol chain extender, and 0.03 g of photoinitiator were added in sequence and ultrasonically stirred for 30 minutes and then added dropwise into a polytetrafluoroethylene mold. The mixture was irradiated with a UV lamp for 30 minutes, moved into a constant temperature drying oven and dried for 24 hours, and the film was cut and placed in a glove box to obtain an electrolyte film.

[0036] Example 2

[0037] This embodiment provides a method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte, comprising the following steps:

[0038] Bromoacetic acid and 1-vinyl imidazole were added to anhydrous acetonitrile in a molar ratio of 1:1, and the reaction was carried out under nitrogen protection for 48 hours. After the experiment, the vacuum filtration was repeated three times with ethyl acetate. After drying at 60°C for 3 days, the carboxylic acid functionalized imidazole chloride (COOH-IL [Cl] ), COOH-IL [Cl] Prepare a 30% aqueous solution, and use a constant pressure funnel to replace anions with a 30% aqueous solution of lithium salt (LiTFSI) of the same substance. After completion, wash it with pure water for 3 times and freeze-dry it for 12 hours to obtain a carboxylic acid functionalized trifluorosulfonic acid imide salt (COOH-IL [TFSI] ). Using lithium hydroxide to react COOH-IL [TFSI] The IL and the photoinitiator were dissolved in anhydrous methanol and irradiated with ultraviolet light for 20 minutes to obtain the polyionic liquid PIL, which was then stored in a vacuum drying oven at 60°C.

[0039] First, use a certain amount of acetonitrile as a solvent to dissolve 1g PEGDA (MW200) and 0.025 PIL, then add 0.05g LITFSI, 0.01g tetrakis(3-mercaptopropionic acid) pentaerythritol (PETMP), 0.0942g thiol chain extender, and 0.05g photoinitiator in sequence, stir ultrasonically for 30 minutes, then add dropwise into a polytetrafluoroethylene mold, irradiate with ultraviolet light for 30 minutes, move into a constant temperature drying oven and dry for 24 hours, cut the film and put it into a glove box to obtain an electrolyte film.

[0040] Example 3

[0041] This embodiment provides a method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte, comprising the following steps:

[0042] Bromoacetic acid and 1-vinyl imidazole were added to anhydrous acetonitrile in a molar ratio of 1:1, and the reaction was carried out under nitrogen protection for 48 hours. After the experiment, the vacuum filtration was repeated three times with ethyl acetate. After drying at 60°C for 3 days, the carboxylic acid functionalized imidazole chloride (COOH-IL [Cl] ), COOH-IL [Cl] Prepare a 30% aqueous solution, and use a constant pressure funnel to replace anions with a 30% aqueous solution of lithium salt (LiTFSI) of the same substance. After completion, wash it with pure water for 3 times and freeze-dry it for 12 hours to obtain a carboxylic acid functionalized trifluorosulfonic acid imide salt (COOH-IL [TFSI] ). Using lithium hydroxide to react COOH-IL [TFSI]The IL and the photoinitiator were dissolved in anhydrous methanol and irradiated with ultraviolet light for 20 minutes to obtain the polyionic liquid PIL, which was then stored in a vacuum drying oven at 60°C.

[0043] Weigh 1.2 g PEGDA (MW5000) to dissolve 0.05 g PIL, then add 0.1 g LITFSI, 0.015 g tetrakis(3-mercaptopropionic acid) pentaerythritol (PETMP), 0.245 g thiol chain extender, and 0.043 g photoinitiator in sequence, stir ultrasonically for 30 minutes, then add dropwise into a polytetrafluoroethylene mold, irradiate with UV light for 30 minutes, move into a constant temperature drying oven and dry for 24 hours, cut the film and put it into a glove box to obtain an electrolyte film.

[0044] The ionic liquid product and the polyionic liquid in Example 1 were subjected to nuclear magnetic resonance. Figure 1 and Figure 2 Analysis of hydrogen spectrum data shows that the product obtained after chemical reaction, washing, and freeze drying has a characteristic hydrogen peak at 9.5ppm after the imidazole N is replaced by bromoacetic acid, and the double peak near 8ppm is the characteristic peak of the H atom on the imidazole ring, and the peaks at 7.5, 5.8 and 5.4ppm are the characteristic hydrogen peaks of C=C on the imidazole ring, and 5.1ppm is the characteristic hydrogen of the carboxylic acid in bromoacetic acid. It is thus determined that the obtained ionic liquid is COOH-IL. The hydrogen spectrum of the polyionic liquid is compared with the ionic liquid monomer. The characteristic peak belonging to C=C is small, and it is replaced by a double peak at 3.0ppm, indicating that free radical polymerization has occurred. Yida ionic liquid has been successfully polymerized.

[0045] The electrolyte films obtained in Example 1, Example 2, and Example 3 were assembled into double stainless steel button cells, and their bulk impedance at room temperature and ionic conductivity at 25°C-75°C were tested. After calculation, the ionic conductivity of the SPE prepared according to the above cases at room temperature was greatly improved compared with the existing PEO-based polymer electrolytes. Figure 3 As shown, it reached 1.35×10 -5 S cm -1 .

[0046] Using LSV to analyze the electrochemical window of the electrolyte, Figure 5 It can be clearly seen that the polymer electrolyte prepared in Example 1 has a withstand voltage window of up to 4.7 V. At the same time, the electrolyte film obtained in Example 1 was assembled into a Li / SPE / Li symmetric battery. 0.1 mA cm -2 The constant current is used to estimate the interfacial stability between the electrolyte and the lithium metal anode. Figure 6As shown, in the first 700 hours, the polarization voltage of the battery was small and stable, indicating that during this period, the plating and stripping of lithium were very stable; even after 700 hours, the polarization voltage began to increase, but the battery continued to charge and discharge stably, and the battery short-circuited only after 1100 hours. Figure 7 As shown in the figure, the pure PEO-based electrolyte underwent severe polarization after running for 400 hours. This shows that the addition of PIL greatly promotes the electroplating and stripping of lithium during the charge and discharge process.

[0047] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte, characterized in that: The steps include: S1. bromoacetic acid and 1-vinylimidazole are added to anhydrous ethanol for reaction, and then dried to obtain carboxylic acid functionalized imidazole chloride; S2. The carboxylic acid functionalized imidazole chloride salt is configured into a 30% aqueous solution, and a 30% aqueous solution of a lithium salt in the same amount is added to the aqueous solution, and the carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imide salt is obtained after drying; S3. adding LiOH solution to the carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imide salt to obtain a hydroxy acid functionalized ionic liquid after reaction; S4. dissolving the hydroxy acid functionalized ionic liquid and the photoinitiator in anhydrous methanol and irradiating with ultraviolet light for 10 to 30 minutes to obtain a polyionic liquid; S5. Add the polyether diene polymer to the polyionic liquid, and then add LITFSI, tetrakis(3-mercaptopropionic acid)pentaerythritol, thiol chain extender, and photoinitiator in sequence, add dropwise into the mold after stirring, and dry after ultraviolet irradiation to obtain a polymer solid electrolyte.

2. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The molar ratio of the bromoacetic acid to 1-vinylimidazole is 1:0.5-1.

5.

3. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The reaction conditions of S1 are: reacting for 40 to 58 hours under nitrogen protection; and the drying conditions are: constant temperature at 55 to 65° C. for 72 to 84 hours.

4. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The molar ratio of the carboxylic acid functionalized imidazole trifluoromethanesulfonic acid imide salt to LiOH in S3 is 1:0.7-1.

7.

5. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The mass ratio of IL to photoinitiator in S4 is 1:0.005-0.

015.

6. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The polyether diene polymer is PEGDA, and its weight average molecular weight is 200-5000.

7. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The thiol chain extender is one or more of 2,3-butanedithiol, 1,6-hexanedithiol, 1,2-ethanedithiol, 2-methyl-3-tetrahydrofuranthiol, and 1,3-propanedithiol.

8. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and 2,4-dihydroxybenzophenone.

9. The method for preparing a polyethylene oxide / amphoteric polyionic liquid composite solid electrolyte according to claim 1, characterized in that: The molar ratio of LITFSI, tetrakis(3-mercaptopropionic acid)pentaerythritol, thiol chain extender, and photoinitiator in S5 is 13.5:2:13.5:0.

01.

10. A solid electrolyte battery obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polyoxyethylene-based solid-state lithium battery positive electrode material, preparation method thereof and battery containing polyoxyethylene-based solid-state lithium battery positive electrode material

    CN117219753A